2000
DOI: 10.1007/s004680000053
|View full text |Cite
|
Sign up to set email alerts
|

Ion exchange reactions on the stem surface of Chamaecyparis obtusa Sieb. et Zucc.

Abstract: In order to clarify the sources of soil acidification below stands of hinoki (Chamecyparis obtusa Sieb. et Zucc.), artificial stemflow experiments were performed to separate out the role rainfall acidity has from that of the acidity potentially occurring during stemflow. Various solutions, including distilled water, NaCl, NH 4 Cl, KCl and CaCl 2 +MgCl 2 solutions, were added in a controlled manner to the upper stem and the solutions systematically collected at breast height. Although the original pH values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The authors concluded that the strong acidity of Japanese cedar was controlled by organic acid supplied from the vegetation, atmospheric SO4 2deposition and partly neutralized by leaching of cations (K + , Ca 2+ , and Mg 2+ ). This mechanism is similar to the stemflow studies of other tree species reported by Fan et al (1999) and Takenaka and Sasama (2000).…”
Section: Stemflowsupporting
confidence: 91%
See 3 more Smart Citations
“…The authors concluded that the strong acidity of Japanese cedar was controlled by organic acid supplied from the vegetation, atmospheric SO4 2deposition and partly neutralized by leaching of cations (K + , Ca 2+ , and Mg 2+ ). This mechanism is similar to the stemflow studies of other tree species reported by Fan et al (1999) and Takenaka and Sasama (2000).…”
Section: Stemflowsupporting
confidence: 91%
“…As a general rule, stemflow pH values for coniferous species are lower than for hardwood species (Takenaka and Sasama, 2000). In particular, IKAWA…”
Section: Ph and Electric Conductivity (Ec)mentioning
confidence: 96%
See 2 more Smart Citations